The Efectiveness of People’s Salt Business Empowerment Program (Pugar) in Demak - Anisa Dwi Ariyani; Siti Hilmiati Azyzia (AFEBI Economic and Finance Review, 2020)
One of Indonesia's coastal areas that have successfully utilize its natural potential is Demak Regency, Central Java. In 2018, Demak Regency Salt production had reached 172,446 tons. The production was driven by government policies in the form of assistance and empowerment of the people's salt business for salt farmers in each village in Demak. This study aims to determine whether the people's salt business empowerment program (PUGAR) has been running effectively or not in Demak Regency, Central Java. The data used in this study were obtained based on survey results and interviews with salt farmers in eleven villages in Demak Regency, Central Java. The research design used accidental sampling to select 32 respondents in Demak. The analytical method used is a qualitative descriptive analysis using several indicators, namely the formation of a community salt business group (KUGAR), channeling assistance from PUGAR to salt farmers, mentoring and training, and also enhancing technology to increase the productivity of salt farmers. The results showed that of eleven villages in Demak District, eight villages had implemented PUGAR programs. However, overall this program has not had a significant impact on the welfare of salt farmers in Demak Regency, Central Java.